2002
DOI: 10.1046/j.1464-5491.2002.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of childhood diabetes in south Asians and other children in Bradford, UK

Abstract: Children in south Asia have a low incidence of Type 1 diabetes but migrants to the UK have similar overall rates to the indigenous population. However, a more steeply rising incidence is seen in the south Asian population, and our data suggest that incidence in this group may eventually outstrip that of the non-south Asians. Genetic factors are unlikely to explain such a rapid change, implying an influence of environmental factors in disease aetiology. The similarity in rates by age group in the south Asian po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 20 publications
3
44
2
1
Order By: Relevance
“…The incidence of type 1 diabetes in children in India and Pakistan is remarkably low [19]. However, a report that focused on an area of the UK with a high south Asian population showed that the incidence of type 1 diabetes increased in south Asian immigrants to the UK from 3.1/100,000 per year to 11.7/ 100,000 per year over a period of just 10 years, thus approaching that of the indigenous population [18,20]. Such a rapid change is unlikely to be explained by genetic factors, implying an influence of environmental factors in disease aetiology.…”
Section: The Prevalence Of Type 2 Diabetes and Cardiovascular Diseasementioning
confidence: 99%
“…The incidence of type 1 diabetes in children in India and Pakistan is remarkably low [19]. However, a report that focused on an area of the UK with a high south Asian population showed that the incidence of type 1 diabetes increased in south Asian immigrants to the UK from 3.1/100,000 per year to 11.7/ 100,000 per year over a period of just 10 years, thus approaching that of the indigenous population [18,20]. Such a rapid change is unlikely to be explained by genetic factors, implying an influence of environmental factors in disease aetiology.…”
Section: The Prevalence Of Type 2 Diabetes and Cardiovascular Diseasementioning
confidence: 99%
“…This seems highly plausible, given the sweeping changes in lifestyle that have affected post-industrial civilisation, the association of type 1 diabetes with an affluent Western style of life, and the increase in prevalence observed in populations migrating from countries with a low incidence to countries with a higher incidence, for example, Asian immigrants to the UK [3]. Since type 1 diabetes is known to have a long prodrome, potential environmental triggers must be sought early in life, and the 'usual suspects' include prenatal or postnatal viral exposure, breastfeeding or other aspects of infant nutrition, and vaccination.…”
Section: A Finger On the Triggermentioning
confidence: 99%
“…For example, it has been shown that children living in South Asia have a low incidence of T1DM, but migrants from there to the United Kingdom have similar overall rates to the indigenous population [7]. Further support for environmental factor influences on the disease derives from the marked geographical variations in T1DM incidence.…”
mentioning
confidence: 97%